Conceptual Approaches and Their Inspiration Sources in Landscape Architecture Design Studio - Sema Mumcu; Tuğba Düzenli (Megaron, 2018)
Inspiration sources play important roles in design process as triggers for idea generation and tools for designers in constructing design problem. In this study understanding how the relationship between design problem and inspiration source is being formed is aimed. The process of Environmental Design Studio V in Karadeniz Technical University, Landscape Architecture Department was examined with a focus on early design phases in which conceptual approaches were determined by using inspiration sources. Design problem solving process was integrated into design studio process and the conceptual approaches determined depending on this process and their inspiration sources were examined. By using different inspiration sources and conceptual approaches, how same project site was resulted in different design products was represented. Concept posters, reports and visuals of application projects submitted by students at the end of the term were used as study materials. By using content analysis method and with a qualitative approach, design concepts and their inspiration sources adopted by students were determined, what kind of variations these concepts created in design solutions-strategies was examined. It was revealed that inspiration sources are directly related to analyses conducted at beginning phases of design; students benefit from ecological, social, cultural and/or physical situations/features, and these sources can be bring forth through functions of building/s located at site, cultural or physical features of the site. Also it was determined that different conceptual approaches to same site directed students to quite varied design scenarios; the activity patterns and space types included in scenarios were also varied in parallel to these differences, by this way authenticity of designs was achieved.